Egypt : Health Sector Reform and Financing Review - World Bank (Washington, DC, 2013)
In 1997, the Ministry of Health and Population (MOHP) of the Government of Egypt (GOE) launched a comprehensive Health Sector Reform Program (HSRP) aiming to develop a national health system, based on social insurance that would address existing problems in equity, access, efficiency, quality and financial sustainability. The purpose of the Health Sector Reform and Financing Review is to provide the GOE and its development partners with a critical assessment of experience to date with the reform. At a critical juncture of the program's life, such an assessment is imperative to inform future phases of the reform and to revalidate, modify, or if necessary revisit the model envisioned at the outset. This study is comprised of five sections: the first sets the background for the study by reassessing the health sector problems that triggered the reform efforts; in the second section, the status of implementation of the HSR Pilot Project will be reviewed in relation to the model envisioned at the outset; section four tries to interpret why implementation of the HSR Pilot Project met, exceeded, or fell short of expectations; in section four, short-term and medium-term reform strategies are proposed aimed at expanding and sustaining the HSR Pilot Project; finally section five concludes the study with a summary of main findings and presents a road map for the future of health sector reform in Egypt.